Mechanistic insight of DACH1 receptor in the development of carcinoma insurgence through MD simulation studies. Issue 2 (26th January 2022) - Hassan, Mubashir; Zahid, Sara; Shahzadi, Saba; Malik, Erum; Zaib, Sumera; Iqbal, Jamshed; Shamim, Saba; Malik, Arif
Abstract: Proteins are key player in the prognosis and therapeutics of carcinomas through the interactions of downstream signalling cascades. Current work insight the structural and mutational analysis of DACH1 in association with carcinogenesis. The homology modelling was employed to predict mutant and wild protein models and their reliability and accuracy was verified through multiple online approaches. Furthermore, MD simulation technique was employed to check the mutation effects on the stability of DACH1 through root mean square deviation and fluctuation graphs. Our results proposed that DACH1 mutation (C188Y) may cause lethal effects and can disturb the DACH1 structure. The observed mutational results showed that C188Y may cause some lethal effect in human body. Based on aforementioned computational assessments, it has concluded that DACH1 could be used as good therapeutic target in the prognosis and therapeutic of carcinoma insurgence. Communicated by Ramaswamy H. Sarma